2015
DOI: 10.1017/s1368980015002463
|View full text |Cite
|
Sign up to set email alerts
|

Maternal caffeine intake during pregnancy and risk of pregnancy loss: a categorical and dose–response meta-analysis of prospective studies

Abstract: Objective: To assess the association between maternal caffeine intake and risk of pregnancy loss using a systematic review and meta-analysis. Design: Categorical and dose-response meta-analysis of prospective studies. Setting: Relevant articles were identified by searching MEDLINE and SCOPUS databases through 30 January 2015. Two authors independently extracted information from eligible studies. Random-effects models were used to derive the summary relative risks (RR) and corresponding 95 % CI for specific cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 81 publications
(153 reference statements)
3
58
2
2
Order By: Relevance
“…The most pronounced effects observed in our study were for caffeine intakes above these guidelines. However, the dose‐response relationship in our and previous studies suggest that the adverse effects of maternal caffeine intake with respect to both pregnancy outcomes and long‐term body fat development are not restricted to high caffeine intakes, but increase across the range of maternal caffeine intake. A review of randomized controlled trials had insufficient evidence to confirm that avoiding caffeine consumption during pregnancy is beneficial with respect to adverse pregnancy outcomes .…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…The most pronounced effects observed in our study were for caffeine intakes above these guidelines. However, the dose‐response relationship in our and previous studies suggest that the adverse effects of maternal caffeine intake with respect to both pregnancy outcomes and long‐term body fat development are not restricted to high caffeine intakes, but increase across the range of maternal caffeine intake. A review of randomized controlled trials had insufficient evidence to confirm that avoiding caffeine consumption during pregnancy is beneficial with respect to adverse pregnancy outcomes .…”
Section: Discussioncontrasting
confidence: 65%
“…As a consequence, fetal exposure to caffeine is prolonged and might adversely influence the development of organ systems. Consumption of caffeine‐containing beverages during pregnancy has been related to an increased risk of fetal death, impaired fetal growth, and low birth weight . In addition to these short‐term outcomes, maternal caffeine intake during pregnancy may also influence long‐term offspring body fat development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After adjusting for pregnancy symptoms, such as nausea and vomiting, other researchers found that consuming doses of 200 mg/day or more still almost doubled the risk of spontaneous abortion. A meta-analysis by Chen et al (126) reported that, compared to a no or very low caffeine intake reference group (0–50 mg/day during pregnancy), every additional 100 mg/day of caffeine (about the amount contained in a typical cup of coffee) increased the risk of pregnancy loss (both miscarriage and stillbirth) by 7% (126). In addition, among women consuming more than 700 mg/day, the risk of pregnancy loss was increased by 72%.…”
Section: Caffeine Toxicitymentioning
confidence: 99%
“…The main harmful effects of caffeine described are related to caffeine consumption during pregnancy. In this particular case, it was described that caffeine increases the risk of pregnancy loss [14] and the risk of low birth weight [15]. Moreover, caffeine consumption during gestation and lactation has profound effects on neuronal development and adult behavior of the offspring [16], and it also alters synaptic proteins during fetal brain development [17].…”
Section: Caffeine: Potential Beneficial Effectsmentioning
confidence: 99%